KAJIAN TEKNOLOGI GASIFIKASI BIOMASSA/SAMPAH UNTUK PRODUKSI SYNGAS DAN LISTRIK BERKELANJUTAN - Muhammad Arief Saputro; Mochamad Syamsiro; Bayu Megaprastio; Feri Febriana Laksana (Jurnal Al Ulum LPPM Universitas Al Washliyah Medan, 2023)
In this modern era, electrical energy is the most needed energy. Because a lot of equipment is powered by electricity. As a result, it must be balanced in relation to the availability of electrical energy. To provide enough electrical energy, a power plant is required. One of the promising technologies in the future is the downdraft gasification technology, where biomass can be used as a very abundant fuel in Indonesia. Rice husk, coconut fiber, coconut shell, palm oil waste, and urban waste are some of the biomass materials used. Based on the results of a literature review regarding the composition and calorific value of the syn-gas produced, the easiest biomass to gasify is a combination of palm fronds/palm fronds (OPF) and palm kernel shells (PKS) with a ratio of 20/80. With this composition ratio, it is possible to produce syn-gas with a composition of 21% CO, 3% CH4, and 17% H2 with a heating value of 5850 kJ/m3. It can be concluded that the type of biomass feedstock greatly influences the composition and calorific value of the syn-gas produced. Because each type of biomass produces different syn-gas characteristics.